EFFECTS OF PURE AND COMMERCIAL PROBIOTIC CULTURES ON GAMMA-AMINOBUTYRIC ACID (GABA) FORMATION AND QUALITY ATTRIBUTES OF THAI FERMENTED PORK SAUSAGE (NHAM) - Phuapaiboon, Pornpan (Food and Feed Research, 2026)
This study investigated the effects of pure and commercial probiotic starter cultures on gamma-aminobutyric acid (GABA) formation and key quality attributes of Thai fermented pork sausage (Nham). Four treatments were prepared: a control without inoculation, a commercial probiotic culture (Starter V3), Lactobacillus plantarum TISTR 543, and Lactococcus lactis subsp. lactis TISTR 1520, with all cultures immobilized on cooked germinated rough rice. Physicochemical properties, including pH, total acidity, and water activity, as well as color, texture, GABA content, and microbial quality, were evaluated during fermentation at 30 °C and during storage at 4 °C. The results showed that probiotic starter cultures significantly enhanced GABA production, with Starter V3 yielding the highest levels, followed by L. plantarum TISTR 543. Probiotic inoculation accelerated acidification, resulting in consistently lower pH values and higher total acidity compared to the control, indicating more efficient fermentation. Lactic acid bacteria counts increased markedly during fermentation and remained high during storage, with   L. plantarum TISTR 543 showing the strongest survival. Textural properties, particularly hardness and gumminess, improved in probiotic-supplemented samples, reflecting enhanced gel formation associated with protein and acid interactions. Although color attributes differed among treatments on the first day of fermentation, these differences diminished thereafter. All treatments met microbiological safety standards throughout fermentation and storage, with no detection of Staphylococcus aureus, Salmonella spp., or Escherichia coli. Overall, the findings confirm that probiotic starter cultures, especially Starter V3 and L. plantarum TISTR 543, can improve fermentation performance, enhance GABA accumulation, and support the development of safe, high-quality Nham with functional health-related potential.